Dysprosium doped copper oxide (Cu1-xDyxO) nanoparticles enabled bifunctional electrode for overall water splitting. (5th August 2021) - Rodney, John D.; Deepapriya, S.; Robinson, M. Cyril; Raj, C. Justin; Perumal, Suresh; Kim, Byung Chul; Krishnan, S.; Das, S. Jerome
Abstract: The production of hydrogen, a favourable alternative to an unsustainable fossil fuel remains as a significant hurdle with the pertaining challenge in the design of proficient, highly productive and sustainable electrocatalyst for both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). Herein, the dysprosium (Dy) doped copper oxide (Cu1-x Dyx O) nanoparticles were synthesized via solution combustion technique and utilized as a non-noble metal based bi-functional electrocatalyst for overall water splitting. Due to the improved surface to volume ratio and conductivity, the optimized Cu 1-x Dy x O ( x  = 0.01, 0.02) electrocatalysts exhibited impressive HER and OER performance respectively in 1 M KOH delivering a current density of 10 mAcm −2 at a potential of −0.18 V vs RHE for HER and 1.53 V vs RHE for OER. Moreover, the Dy doped CuO electrocatalyst used as a bi-functional catalyst for overall water splitting achieved a potential of 1.56 V at a current density 10 mAcm −2 and relatively high current density of 66 mAcm −2 at a peak potential of 2 V. A long term stability of 24 h was achieved for a cell voltage of 2.2 V at a constant current density of 30 mAcm −2 with only 10% of the initial current loss. This showcases the accumulative opportunity of dysprosium as a dopant in CuO nanoparticles for fabricating a highly effective and low-cost bi-functional electrocatalyst for overall water splitting. Graphical abstract: Image 1 Highlights: The OER activity for Cu0.98 Dy0.02 O was found to be 1.53 V vs RHE at 10 mAcm −2 . The HER activity for Cu0.99 Dy0.01 O was found to be −0.18 V vs RHE at −10 mAcm −2 . The two-electrode electrolyzer posted a cell voltage of 1.56 V at 10 mAcm −2 . The long-term stability of the setup was found to be 2.15 V@30 mAcm −2 for 24 h.